SUBAERIAL EXPOSURE SURFACES IN A PALAEOPROTEROZOIC 13C-RICH DOLOSTONE SEQUENCE FROM THE PECHENGA GREENSTONE BELT: PALAEOENVIRONMENTAL AND ISOTOPIC IMPLICATIONS FOR THE 2330-2060 MA GLOBAL ISOTOPE EXCURSION OF 13C/12C - Melezhik V.A.; Fallick A.E.; Grillo S.M. (My University, 2004)
This article reports the discovery of numerous subaerial exposure surfaces which occur in the ca. 2200 Ma Kuetsjärvi Sedimentary Formation (KSF) from the Pechenga Greenstone Belt, NE Fennoscandian Shield, Russia. The formation was accumulated within an intraplate rift and is composed of fluviatile-deltaic siliciclastic deposits and lacustrine dolostones. The dolostones are enriched in ( to +7.6‰ V-PDB, to 21.5‰ V-SMOW), which is, in general, assigned to a global perturbation of the carbon cycle. The lacustrine dolostone unit contains desiccated and in situ brecciated carbonate beds, subaerial erosion and dissolution surfaces, epikarst, surficial silicification (silcretes) and hot-water spring travertines. The dissolution surfaces—marked by formation of a few centimetre thick, ‘vuggy’, non-laminated, dolomicrite capped by silicified nodular zone—resemble modern calcretes which formed by capillary rise of surface waters (per-ascensum calcrete) following saturation of the regolith zone under arid or semi-arid conditions. Abundant red, iron-stained, superficial dolocrete implies the existence of an O2-rich atmosphere. Rezolith, ‘black pebbles’, alveolar septal structures, ‘Microcodium’ and other fabrics associated with plant roots and input of terrestrial organic matter, which are typical for post-Cretaceous pedogenic calcretes, have not been identified. Alfa fabrics can be applied to describe dolocretes though rhombic calcite crystals are lacking. Neither 13C-depletion nor 13C-enrichment has been documented in the dolocrete, which suggests no contribution of CO2 derived from soil or from any other Corg-rich sources enriched in 12C, and apparent lack of biological uptake of 12C during formation of the dolocrete. Both petrographic and carbon isotope data do not support earlier assertions that Palaeoproterozoic subaerial surface was colonised by microbial mats. A few samples have high values (up to 30‰) despite diagenetic and metamorphic resetting of the oxygen isotope system, suggesting evaporation during formation of the superficial dolocrete. Such documented episodes of subaerial exposure, formation of hot-water travertines, superficial dolocrete and silcrete suggest that there must have been frequent decoupling between the Kuetsjärvi depositional system and the bordering sea. This imposes an additional restriction on the use of the isotopic composition of the KSF dolostones for reconstruction of the global secular curve.
Keywords: Palaeoproterozoic; Lacustrine; Dolocrte; Silcrete; Dolostone; Carbon and oxygen isotopes; Subaerial exposure surface; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская